Prevalence of attention deficit hyperactivity disorder in relation to the sex of school children Prevalência de transtorno de déficit de atenção/ hiperatividade em relação ao gênero de escolares - Cardoso F.L.* (2007)
The main objective of this research was to verify possible gender-based differences in the subtypes of ADHD. It was a descriptive-exploratory and non-probabilistic study. Eighty-four children aged between 6 and 16years were indicated for participation by their teachers, and the DSM-IV and EDAH scale assessments were then applied. Seventy-one participants were identified as positive by at least one of these scales, as a result of which 51 boys and 20 girls were enrolled on the study, at an average of 3.5 boys for each girl. This study upholds the results of the literature review in terms of ADHD prevalence among boys. This difference is probably the result of the prevalence among girls being underestimated due to more inattention symptoms than hyperactivity behavior.